2011
DOI: 10.1111/j.1439-0485.2011.00484.x
|View full text |Cite
|
Sign up to set email alerts
|

Microhabitat distribution of Smacigastes micheli (Copepoda: Harpacticoida: Tegastidae) from deep‐sea hydrothermal vents at the Mid‐Atlantic Ridge, 37° N (Lucky Strike), with a morphological description of its nauplius

Abstract: Abundant nauplii and copepodid stages attributed to Smacigastes micheli Ivanenko & Defaye (Crustacea: Copepoda: Harpacticoida: Tegastidae) were collected during the MoMARETO cruise (2006) on the Eiffel Tower edifice, the species type locality at the Lucky Strike vent field (37° N) of the Mid‐Atlantic Ridge at a depth of 1698 m. Specimens were sampled within different faunal assemblages dominated by either Bathymodiolus azoricus mussels or Mirocaris fortunata shrimps and the physico‐chemical conditions of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Among the known copepod vent taxa, Smacigastes micheli, previously described for the Lucky Strike vent field, probably feeds on microbial mats and detritus (Ivanenko et al, 2012), which might explain its high densities on panels A2-B2 and possibly on B3. Tisbe spp.…”
Section: Vent Endemicsmentioning
confidence: 84%
See 1 more Smart Citation
“…Among the known copepod vent taxa, Smacigastes micheli, previously described for the Lucky Strike vent field, probably feeds on microbial mats and detritus (Ivanenko et al, 2012), which might explain its high densities on panels A2-B2 and possibly on B3. Tisbe spp.…”
Section: Vent Endemicsmentioning
confidence: 84%
“…Copepod individuals were dissected under a Leica MZ12 microscope and studied with a Leica DMR compound microscope having bright-field and differential interference contrast optics. The nauplii were studied by applying the "hanging drop method" for light microscopy (see Ivanenko et al, 2012).…”
Section: Experimental Design and Sample Collectionmentioning
confidence: 99%
“…For confocal microscopy, exoskeletons were individually transferred to distilled water and then stained with Fuchsin (Ivanenko et al 2012; Corgosinho et al 2018). The copepods were inspected using an inverted Nikon A1 confocal laser scanning microscope (CLSM, Nikon Corporation, Tokyo, Japan) at Lomonosov Moscow State University, using a 40× oil immersion objective and lasers with wavelengths of 532 and 640 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Little information and data on the effects of "moderate" environmental variation on the hydrothermal fauna are available for vent ecosystems. Several studies suggested that there is a strong link between faunal distribution, population dynamics and hydrothermal environmental conditions (Sarrazin et al, 1999, Govenar and Fisher 2007, Cuvelier et al, 2009, Ivanenko et al, 2012, Sen et al, 2013, supporting the idea that the fauna respond quickly to "abiotically challenging" environments (Girguis and Lee, 2006). Modifications in fluid flow may influence resource availability (De Busserolles et al, 2009, Beinart et al, 2012) by inducing changes in microbial production (Guezenec et al, 1998;Sievert et al, 2000) and/or the abundance of symbionts (Halary et al, 2008;Robidart et al, 2011).…”
Section: Links Between Faunal Distribution and Environmental Conditiomentioning
confidence: 98%